The efficiency removal of phosphorus by using recycled concrete aggregate (RCA) as filter - A Roni, Norwardatun; Adnan, Suraya Hani; Hamdan, Rafidah (Penerbit Uthm, 2018)
Phosphorus (P) is a main nutrient element plants growth in natural water system. However, excessive P loads to water bodies from industrial, agricultural, household wastes may cause the overgrowth of aquatic plants or algae which accelerate the depletion of dissolved oxygen (DO) in waters, and leading to serious eutrophication problems. In developing countries, approximately 75% of domestic wastewater is released to the environment without treatment (Rozari et al. 2016). Ayaz et al. (2012) reported that eutrophication in receiving water bodies may occur when concentration of phosphorus was 6 mg/L. Therefore, proper treatment to remove phosphorus from domestic wastewater to achieve the admissible level for natural systems is needed. Besides, construction and demolition (C&D) activities shows a growing trend for several years.